FEMALE ULAMA: MEDIATING RELIGIOUS AUTHORITY IN A LIMITED ‘ISLAMIC’ PUBLIC SPHERE IN CONTEMPORARY INDONESIA - Muhammad Irfan Hasanuddin (Islam Realitas: Journal of Islamic and Social Studies, 2018)
Religious authority and the viable role played by female ulama in a limited Islamic public sphere have always been a matter of concern. Unlike previous studies focused much on gender sensitive, this research will analyze crucial position of Islamic public sphere in which female santri of Ma’had ‘Ali As’adiyah South Sulawesi can build and transform their authority. The research argues the decrease level of female authority is due to their lack of involvement in limited Islamic public sphere within and outside pesantren. Drawing on female santris’ daily activities, particular attention will be given to how female As’adiyah achieve, harness, build and transform religious authority through mosque and classroom environment. This reveals that authority of female ulama has not exclusively to do with the mastering of classical Islamic knowledge, but also with the maximizing the use of a limited ‘religious’ public sphere which is represented in halaqah of mosque, preaching stage, and the production of hybrid knowledge within classroom environment.